The Gershwins and me a personal history in twelve songs - Feinstein, Michael 1956- (Simon & Schuster, 2012)
Michael Feinstein was just 20 years old when he got the chance of a lifetime: a job with his hero, Ira Gershwin. During their six-year partnership, Feinstein blossomed under Gershwin's mentorship and Gershwin was reinvigorated by the younger man's zeal. Now, in The Gershwins and Me, Michael Feinstein shares unforgettable stories and reminiscences from the music that defined American popular song, along with rare Gershwin memorabilia he's collected through the years. Includes an accompanying CD packed with Feinstein's original recordings of 12 Gershwins' songs